"The Savage Heart beneath the Civilized Exterior": Race, Citizenship, and Mental Illness in Washington, D.C., 1900-1940 - Gambino, Matthew (Disability Studies Quarterly, 2008)
During the early decades of the twentieth century, William Alanson White and the medical staff at St. Elizabeths Hospital in Washington, D.C. developed an ambitious program for U.S. psychiatry in which the profession would be dedicated to the reconstitution of mentally-fit and socially-productive American citizens. The racist assumptions beneath this program led most psychiatrists at the institution to expect little more than deference, dependence, and common labor from their black patients, preventing them from comprehending the impact of substandard and racially-segregated care. Black men and women were acutely aware of the injustices they faced. When they rejected elements of the hospital's medical regimen, these patients were also rejecting a social vision that consigned them to the margins of American civic life.